Investigating a common approach to DNA profile interpretation using probabilistic software. (May 2015) - Cooper, Stuart; McGovern, Catherine; Bright, Jo-Anne; Taylor, Duncan; Buckleton, John
Abstract: Recently there has been a drive for standardisation of DNA profile interpretation within and between different forensic laboratories. The continuous interpretation software STRmix™ has been adopted for use by laboratories in Australia and New Zealand for profile interpretation. Within this paper we examine the concordance in profile interpretation of three crime samples by twenty different analysts across twelve different international laboratories using STRmix™. The three profiles selected for this study exhibited a range of template and complexity. The use of probabilistic software has compelled a level of concordance between different analysts however there remain differences within profile interpretation, particularly with the objective assignment of the number of contributors to profiles.